Genistein-induced mir-23b expression inhibits the growth of breast cancer cells - Avci, Cigir Biray; Susluer, Sunde Yilmaz; Caglar, Hasan Onur; Balci, Tugce; Aygunes, Duygu; Dodurga, Yavuz; Gunduz, Cumhur (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: Genistein, an isoflavonoid, plays roles in the inhibition of protein tyrosine kinase phosphorylation, induction of apoptosis, and cell differentiation in breast cancer. This study aims to induce cellular stress by exposing genistein to determine alterations of miRNA expression profiles in MCF-7 cells. Material and methods: XTT assay and trypan blue dye exclusion assays were performed to examine the cytotoxic effects of genistein treatment. Expressions of miRNAs were quantified using Real-Time Online RT-PCR. Results : The IC 50 dose of genistein was 175 μM in MCF-7 cell, line and the cytotoxic effect of genistein was detected after 48 hours. miR-23b was found to be up-regulated 56.69 fold following the treatment of genistein. It was found that miR-23b was up-regulated for MCF-7 breast cancer cells after genistein treatment. Conclusions : Up-regulated ex-expres-sion of miR-23b might be a putative biomarker for use in the therapy of breast cancer patients. miR-23b up-regulation might be important in terms of response to genistein.